ESENSI KURUKULUM DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Harahap, Muhammad Yunan (Jurnal Ilmiah Al-Hadi, 2018)
Discussion of the curriculum based on the philosophy of Islamic education is a must, because the philosophy of Islamic education is a compass and foundation for various kinds of educational activities and activities in order to achieve educational goals. The necessity of discussing the perspective of Islamic education philosophy is to avoid the obscurity and obscurity of the curriculum. Explanation of the path of light (manhaj), suggests that the curriculum is an educational tool that must be taken integrally to achieve educational goals. As Islam considers that the purpose of education is to shape a person's personality that makes him a human being, with the pattern of piety, we mean that people are spiritually and physically intact, able to live and develop naturally and normally because of their submission to Allah SWT. This paper is entitled The essence of the curriculum in the perspective of Islamic education philosophy, which will discuss the understanding, branches, principles, and urgent matters concerning the curriculum in the realm of philosophy.